Back lobe reduction of aperture coupled microstrip antenna / Hafiza Alias - Alias, Hafiza (2015)
A novel design of 2 by 2 aperture coupled microstrip antenna (ACMSA) with back lobe reduction and gain enhancement is presented in this thesis. The basic design of the proposed antenna uses a 2 by 2 planar array structures with aperture coupler feeding technique. Both of the substrates are Rogers Duroid 5880 of thickness 0.787mm with dielectric constant of 2.2 and named as Structure 1. Electromagnetic Band Gap (EBG) is first integrated onto the antenna, Structure 2, via two approaches; by placing them onto the feedline layer and also onto the patch layer to study and analyze the effect on the ACMSA. The gain of the antenna slightly improved but the back radiation does not give any good reduction. Next, the Defected Ground Structure (DGS) concept was proposed in Structure 3 to realize the back radiation reduction effect. Four DGS with dumbbell shape were etched on the ground plane, which is sandwiched between the upper and lower substrates. Structure 4 was introduced as twelve trapezoidal-shaped parasitic elements are placed onto the first substrate, three elements besides each patch of Structure 3. The antenna design is simulated in CST Microwave Studio software with operating frequency of 5.8 GHz. The results show that back lobe level is reduced from 4.6 dB to -0.06 dB. The gain of the antenna dropped from 11.8 dB to 11.2 dB when DGS is added. However with the parasitic element, the gain is improved to 11.5 dB. An improvement can be seen to the front-toback ratio of the antenna. With the addition of DGS and parasitic element, the ratio improves from 7.2 dB to 11.37 dB. Return loss of the antenna is -27.50 dB. This design concept can be useful in reducing the back radiation of aperture coupled microstrip antenna and improve the front-to-back ratio.